Karnataka Beyond the Three-Language Formula: Shaping India’s Multicultural Future, Viksit Bharat@2047 - Nandan J.C.; Sudarshanagouda M. Patil (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
India has always been known for the diversity, which has become the beauty of the country. In this linguistic diversity is also notable. India came up with THE THREE LANGUAGE FORMULA in the year 1968 focusing on bringing a balance between preserving different regional languages in the country and strengthening Hindi as a link language and English for global access. Even after having this idea for nearly seven decades, it has faced repeated disagreements, with states like Tamil Nadu outright rejecting it and others negotiating their own interpretations. In this larger debate, Karnataka has recently shifted towards a TWO-LANGUAGE policy, which has become a national discussion again. This paper examines Karnataka as a case study to explore how India’s Multi-lingual future can be reimagined, as the country moving towards 2047 which marks the 100 years of independence. By revisiting historical events like linguistic state principle [1956] and the strong resistance shown by PERIYAR who warned Hindi domination would lead to cultural slavery and destroy equality among Indians. Here the paper sheds light on policy choice within a wider historical and political framework. And it also talks about international perspectives from UNESCO [2003] statement.